2014
DOI: 10.1161/circep.113.001219
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Contact Force During Endocardial and Epicardial Ventricular Mapping

Abstract: Background— The optimal contact force (CF) for ventricular mapping and ablation remains unvalidated. We assessed CF in different endocardial and epicardial regions during ventricular tachycardia substrate mapping using a CF-sensing catheter (Smartouch; Biosense-Webster) and compared the transseptal versus retroaortic approach. Methods and Results— In total, 8979 mapping points with CF, and force vector orientation (VO) were recorded in 21… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 15 publications
1
33
0
Order By: Relevance
“…Multiple important studies have been reported within the last 12 months documenting the importance and increased utilization of VT ablation. Despite several remarkable technical and technological improvements and innovations such as use of image integration, 26 novel ablation electrodes, 27,28 forcesensing technologies, 29 or ultra-high density mapping, 30 the relatively high recurrence rate of any VT after catheter ablation in patients with VT and structural heart disease remains a key challenge. As evident from recent multi-centre data, non-inducibility of any VT at the end of the ablation is probably the best endpoint for the procedure and should be targeted.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple important studies have been reported within the last 12 months documenting the importance and increased utilization of VT ablation. Despite several remarkable technical and technological improvements and innovations such as use of image integration, 26 novel ablation electrodes, 27,28 forcesensing technologies, 29 or ultra-high density mapping, 30 the relatively high recurrence rate of any VT after catheter ablation in patients with VT and structural heart disease remains a key challenge. As evident from recent multi-centre data, non-inducibility of any VT at the end of the ablation is probably the best endpoint for the procedure and should be targeted.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathmentioning
confidence: 99%
“…These and other issues are elegantly described in the 2015 updated version of the European Heart Rhythm Association practical guide, 21 following the great success of its first version published in 2013. 29 or ultra-high density mapping, 30 the relatively high recurrence rate of any VT after catheter ablation in patients with VT and structural heart disease remains a key challenge. As evident from recent multi-centre data, non-inducibility of any VT at the end of the ablation is probably the best endpoint for the procedure and should be targeted.…”
mentioning
confidence: 99%
“…Although the presence of epicardial fat has a considerable modifying effect on lesion formation, the catheter also has a more parallel orientation on the epicardial surface, so that the applied CF has a greater lateral than axial component, resulting in altered lesion geometry. 46,47 Such force vector information could be useful to prevent pulmonary lesions during epicardial RF ablation. 47 These insights have recently been reported to be helpful for successful CF-guided endocardial and epicardial ablation of ventricular tachycardia.…”
Section: Catheter Cf For Mapping and Ablation Of Ventricular Arrhythmiasmentioning
confidence: 99%
“…Although the optimal CF for ventricular mapping and ablation has yet to be determined, in this issue of Circulation: Arrhythmia and Electrophysiology, Jesel et al 6 provide important insights into regional variations in CF and catheter orientation relating to epicardial and endocardial mapping. Briefly, the authors evaluated CF variability using a cooled-tip mapping/ablation catheter (Thermocool SmartTouch, Biosense Webster, Inc, Diamond Bar, CA) during endocardial and epicardial mapping in a cohort of patients with and without structural heart disease undergoing catheter ablation of VT, by 2 experienced operators blinded to the collected CF data.…”
Section: Article See P 1168mentioning
confidence: 99%
“…Further research is needed to enhance our understanding and interpretation of the available data in the hopes of continuing to improve the outcomes from VT ablation. As such, the article by Jesel et al 6 represents an excellent starting point.…”
Section: Circ Arrhythm Electrophysiolmentioning
confidence: 99%